Bevacizumab: Renal Safety Evaluation. Issue 3 (November 2017) - Fenoglio, Roberta; Roccatello, Dario
Angiogenesis is a key physiologic process for growth and development. Vascular endothelial growth factor (VEGF) has been identified as an angiogenic activator. It regulates several normal physiologic and pathologic processes including malignancies. The VEGF family and their receptors (VEGFR) are important mediators of tumor angiogenesis. Blocking tumor angiogenesis has become an increasingly attractive modality for anticancer therapy. Bevacizumab (BVZ), a humanized monoclonal immunoglobulin, has been approved to treat many types of cancers. However, the inhibition of VEGF results in a predictable pattern of adverse events, including renal toxicities. Published data regarding the BVZ renal safety are not yet definitive. In this review, the BVZ renal safety profile will be discussed, together with the peculiarities related to its use in patients undergoing dialysis or even in patients with renal transplant. Patients treated with BVZ have an increased risk of hypertension and proteinuria that may vary with dosage, cancer types, and concomitant drugs. The kidney lesions that may be secondary to bevacizumab are not completely known. New expert opinions will be possible if the number of kidney biopsies increased. The published data suggest that BVZ-based therapy is associated with reasonable and accepted renal toxicity if close monitoring and correct management are performed.